Laboratory analogues of Martian electrostatic discharges - Aplin, K; Goodman, T; Herpoldt, K; Davis, C (2012)
Electrical discharges in Martian analogue materials have previously been generated by agitation of the material in a low-pressure carbon dioxide environment. These results have led to the supposition that lightning is likely on Mars, on the basis that the surface material becomes triboelectrically charged, and the charges are then gravitationally separated in dust storms. We have reproduced one of these experiments and find that triboelectric charging of the Martian regolith simulant by the walls of the vessel used can adequately explain all the effects observed. Our results indicate that unless special care is taken to avoid wall effects, the electrostatic properties of a laboratory system cannot be extrapolated to the Martian environment. We also note that charging of the outside of the vessel used can generate transients within the vessel which could be mistaken for electrical discharge signals, unless accompanied by optical emissions. © 2012 Elsevier Ltd. All rights reserved.